The Impact of a Circular Economy on Sustainable Development - Kazimierz Górka; Marcin Łuszczyk; Agnieszka Thier (Barometr Regionalny, 2019)
The issue of the exhaustibility and limited of natural resources has been noticed, among others, as a result of intensive economic development and civilization progress. In the second half of the 20th the emission of industrial and municipal pollutants, mainly as a result of burning fossil fuels, also became a serious problem. The article presents the essence and manifestations of the economy in a closed circuit and its impact on shaping sustainable socio-economic development, as well as the analysis of the possibilities of implementing these principles in business practice and in everyday life. According to the authors, managing in a closed circulation appears to be the highest stage of civilization development. Closing the so-called the loop and the economic cycle is becoming real in many areas as a result of extending the life cycle of products, the use of an ever-wider range of waste as secondary raw materials — instead of primary raw materials, the use of renewable energy sources, rationalization of water and forest management, etc.